Between Freedom And Protection: A Critical Review Of Indonesia’S Cyberspace Law - Haekal Al Asyari (Prophetic Law Review, 2023)
Following the COVID-19 pandemic, dependency on the internet—notably, the utilization of cyberspace—has increased, amplifying the virtual domain to a prominent role in everyone’s everyday life. As a country with one of the highest number of internet users in Asia, Indonesia faces challenges of unequal access, limits on content, data privacy, data security, and digital literacy. Given that cyberspace infrastructure is shared between governments, corporations, individuals, and telecommunication providers while individual countries govern the networks, the Indonesian government is under its own exclusive authority to legislate and create policies governing Indonesia’s cyberspace. There has been significant progress toward a legal framework of Indonesia’s cyberspace law, such as the enactment of the Personal Data Protection Law. Unfortunately, such progress is far from being effective. It is evident from Indonesia’s fragmented laws, response-driven policies, and the numerous cyber incidents that have occurred only within the past years. This article investigates Indonesia’s legal-philosophical position in governing the cyberspace. By using a normative methodology, this research crystallizes Indonesia’s position between the freedom or the protectionist approach through analyzing the existing cyberspace regulations. The result of this study shows that Indonesia is somewhere in the middle of liberalizing its cyberspace and protecting it for its national interest. This position could bring both advantages and disadvantages to Indonesia’s cyberspace development. Keywords: Cyberspace, Freedom, Indonesia, Protection.